Analysis of Gabapentin's Efficacy in Tinnitus Treatment: A Systematic Review. (March 2022) - Tavares, Matheus Pedrosa; Bahmad, Fayez
Objectives: Tinnitus can be a chronic symptom that brings disability and distress. Some studies suggested that gabapentin might be effective on tinnitus relief. The objective of the study is to perform a systematic review in order to evaluate the efficacy of oral gabapentin in patients with tinnitus. Methods: A literature search was conducted in English and following the recommendations from PRISMA. The terms used were: ("tinnitus" OR "subjective tinnitus") AND ("gabapentin"). The study selection was performed following the eligibility criteria in accordance to the PICOS (population, intervention, comparison, outcome, study design) strategy—patients with tinnitus; oral gabapentin; placebo; reduction of tinnitus severity questionnaires scores; prospective, double-blind, randomized controlled trial, respectively. The selected studies were included in qualitative synthesis. The studies were analyzed according to Joanna Briggs Institute's critical appraisal checklist for randomized controlled trials. Results: One hundred twenty-one studies were found in 9 databases and 8 studies were found in gray literature. After study selection, 6 articles were read in full. Then, 2 studies were excluded and 4 were included in qualitative synthesis. All 4 articles were analyzed according to critical evaluation checklist. Conclusions: There is insufficient evidence to recommend the use of gabapentin for patients with tinnitus.